Advances in the mechanical characterization of ski-boots - Petrone, N. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The need of a standard definition of bending properties of ski-boots, buckle closure, testing procedure and data analysis was addressed by the ongoing research: preliminary results will indicate several lines of further research.